Indigenous Indonesian Dayak Traditional Wisdom in Reducing Deforestation - Sidik R. Usop; Ismi Rajiani (Faculty of Geography, Universitas Gadjah Mada, 2021)
The function of forests for Dayak people is not only to fulfill the needs of life but also related to the ancient belief to preserve natural resources. The study aims to analyze the traditional model of protecting the conservation area by applying surveys and in-depth interviews. In this particular case study, a set of values – batang garing (tree of life), belom bahadat (living compliant with customary law), pali (taboo) ,manyanggar (asking the consent of the ancestor),memapas lewu (brushing the village) – central to the Dayak Ngaju people, the indigenous population in Central Kalimantan, become contested in the course of the economic and development project. Adherence to these central values creates movement to prevent damage to indigenous people's natural resources under the tag “Manyalamat Petak Danum” (Saving our homeland).